Optimisation of zinc ion removal from aqueous solution by rice husk biosorbent - Jusoh, Mohamad Shafiq (2018)
In this study, adsorption of zinc ion from aqueous solution using rice husk biochar as adsorbent was investigated. Batch adsorption studies were carried out to study the response of independent variables as well as the interaction between different parameters in a system with minimal experimental runs. This study consist of three parameters which were initial concentration of zinc ion in aqueous solution (10 mg/L to 30 mg/L), adsorbent dosage (0.5 g to 1.1 g), and contact time (5 minutes to 25 minutes) while the response is zinc ion removal (%). Optimisation studies were performed by using response surface methodology (RSM) and employing central composite design (CCD). The correlation coefficient, R2 for the response were 0.9325. The interaction between parameters were studied using 2D contour plot and 3D response surface graph. Optimum zinc ion removal predicted by RSM were found to be 94.33%, with the conditions of 21.72 mg/L initial concentration, 0.98 g of adsorbent dosage and contact time of 24.97 minutes at desirability of 1.0.